Characterization of a Robust CoII Fluorescent Complex Deposited Intact On HOPG1. Issue 33 (2nd July 2014) - Heras‐Ojea, María José; Mañeru, Daniel Reta; Rosado, Lidia; Zuazo, Juan Rubio; Castro, German R.; Tewary, Subrata; Rajaraman, Gopalan; Aromí, Guillem; Jiménez, Erika; Sañudo, E. Carolina
Abstract The new diimine fluorescent ligand ACRI‐1 based on a central acridine yellow core is reported along with its coordination complex [Co2(ACRI‐1)2] (1), a fluorescent weak ferromagnet. Due to the strong fluorescence of the acridine yellow fluorophore, it is not completely quenched when the ligand is coordinated to CoII. The magnetic properties of bulk complex 1 and its stability in solution have been studied. Complex 1 has been deposited on highly ordered pyrolitic graphite (HOGP) from solution. The thin films prepared have been characterized by AFM, time‐of‐flight secondary ion mass spectrometry (TOF‐SIMS), grazing incidence X‐ray diffraction (GIXRD), X‐ray absorption spectroscopy (XAS), X‐ray magnetic circular dichroism (XMCD) and theoretical calculations. The data show that the complex is robust and remains intact on the surface of graphite.